Real-time measurement and estimation of factory CO2 emissions - Karlsson, Conny (My University, 2021)
The motivation for the thesis was to investigate the feasibility of creating a dynamic system for displaying caused CO2 emissions from a factory environment. Nordkalk’s factory in Parainen, Finland, was used to provide real process data to aid in the research. This research topic required the thesis author to acquire deep knowledge and understanding of the methods to obtain the necessary data and of the technologies required to implement such as system. The information was collected from sources such as literature, factory process data, technology manuals and reference data. Based on this information, key components of the system were created, which made use of the collected process data. Research was done regarding the use of both measured and estimated power usage and caused CO2 emissions data and the feasibility of estimation. The implemented system components made use of technologies such as .Net Framework, C# language, SQL, OPC UA and SVG graphics. The components implemented the factory process data recording and visualization of the data. Manual analysis was done to evaluate the possibility of estimating CO2 emissions. The result of the thesis research, shows that it is possible to create a dynamic open system, which could provide detailed information on caused CO2 emissions in a factory context, that could be used together with other systems such as MES systems to create further added-value.
Keywords: CO2,emissions,data collecting,measurement,estimation,MES,factory,process,production,climate change